Knowledge of brucellosis epidemiology to support the development of a national brucellosis strategy to support 45 million Kenyans - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
After years of advocacy and integrated field research by CGIAR and other partners, the Government of Kenya prioritized brucellosis as a neglected zoonoses for government attention and a draft National Strategy for Brucellosis was recently finalized. With a national strategy, new combined health and livestock sector policies for brucellosis surveillance and control can be implemented by government administrations, public and private sector hospitals, and NGOs. The result will be better patient management and reduced use of tertiary antibiotics.